Cooperative Learning sebagai Strategi Penguatan Sikap Toleransi dalam Pembelajaran Al-Qur'an Hadis - Afwan Irsyadi; Ah. Haris Fahrudi (Jurnal Bilqolam Pendidikan Islam, 2026)
This study aims to analyze the implementation of Cooperative Learning in Al-Qur'an Hadith learning and examine its role in strengthening students' tolerance attitudes at SMK Sunan Giri Driyorejo. The study employed a qualitative approach using a case study design. Data were collected through interviews, observations, and documentation involving an Al-Qur'an Hadith teacher, the vice principal for curriculum affairs, and students. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings reveal that Cooperative Learning was implemented through heterogeneous group formation, group discussions, presentations, and reflective learning activities. This learning model created a participatory and collaborative learning environment that enabled students to interact, exchange ideas, and work together in completing learning tasks. The development of tolerance attitudes was reflected in students’ ability to respect differing opinions, listen to others’ perspectives, accept diverse personal characteristics, demonstrate empathy, and build cooperation within learning groups. Supporting factors included a religious school culture, teacher support, and a collaborative learning environment, while inhibiting factors consisted of students’ tendency to choose particular peers and unequal participation during group discussions. The study demonstrates that Cooperative Learning functions not only as an instructional strategy to enhance student engagement but also as a mechanism for internalizing tolerance values and strengthening religious moderation in Al-Qur'an Hadith learning. These findings contribute to the development of Islamic Religious Education by highlighting the role of Cooperative Learning in fostering tolerance through structured social interaction and collaborative learning experiences.